Metformin Adjunct With Antineoplastic Agents for the Treatment of Lung Cancer: A Meta-Analysis of Randomized Controlled Trials and Observational Cohort Studies - Luo, Xiaofeng; Chen, Xi; Wang, Lin; Yang, Bowen; Cai, Shuang (Frontiers in Pharmacology, 2021)
Objective: Resistance to anticancer agents ensures a poor prognosis in patients with lung cancer. Metformin could enhance the anticancer effects of standard antineoplastic agents [traditional chemotherapy drugs, epidermal growthfactor receptor-tyrosine kinase inhibitors (EGFR-TKIs), or immune checkpoint inhibitors (ICIs)]; however, it is unclear whether metformin can be combined with antineoplastic agents in the treatment of lung cancer. To explore the efficacy of combinational strategies, we performed a systematic review and meta-analysis for diabetic and nondiabetic patients with lung cancer. Method: An electronic literature search was performed to obtain relevant randomised controlled trials (RCTs) and observational cohort studies. Hazard ratios (HR) with 95% confidence intervals (CI) of overall survival (OS) and progression-free survival (PFS) outcomes were extracted. Subgroup analysis by antineoplastic agents, study type and histology were investigated. Results: Fourteen studies (three RCTs and eleven observational cohort studies) consisting 3856 patients were included in the meta-analysis. Compared to standard antineoplastic agents alone (traditional chemotherapy drugs, EGFR-TKIs or ICIs), the antineoplastic agents combined with metformin significantly improved OS (HR 0.73, 95% CI 0.66–0.81, P<0.00001) and PFS (HR 0.72, 95% CI 0.59–0.88, P=0.001); a similar association was found in observational evidence. Limited data from RCTs showed no differences in OS or PFS. Conclusion: Metformin plus antineoplastic agents may improve survival outcomes of patients with lung cancer. Further investigation is needed.